Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.18805/ag.r-2520
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management in Millets- A Holistic Approach

Abstract: Millets are the traditional staple food of dry land regions and have the potential to contribute substantially for food, fodder and the nutritional security. The millets are relatively poor competitors against weeds especially during the early growth stages due to their slow initial growth and wider spacing. Yield loss due to weeds in millets varies from 5 to 94 per cent depending on climatic, edaphic and biotic factors. Weeds compete with crops for nutrients, soil moisture, sunlight and space when they are li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…In minor millets the herbicide recommendations have been limited. Sneha and Raj [24] concluded that Saflufenacil (Kixor) @ 0.05 kg/ha as Pre emergence and 2,4-D (Weedar) @ 0.50-0.75 kg/ha as Post emergence in proso millet, Oxadiazone (Ronstar) @ 0.75-1.0 and Butachlor (Mechete) @ 0.75 kg/ha as Pre emergence in finger millet, Isoproturon (Arelon) @ 0.50-0.75 kg/ha as Pre emergence in Finger mille and kodo millet, Propazine (Propinex)@ 0.28-0.56 kg/ha as Pre emergence in Proso millet are recommended herbicides in minor millets. Atrazine was the most commonly used preemergence herbicide for weed control in millets.…”
Section: (D) Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In minor millets the herbicide recommendations have been limited. Sneha and Raj [24] concluded that Saflufenacil (Kixor) @ 0.05 kg/ha as Pre emergence and 2,4-D (Weedar) @ 0.50-0.75 kg/ha as Post emergence in proso millet, Oxadiazone (Ronstar) @ 0.75-1.0 and Butachlor (Mechete) @ 0.75 kg/ha as Pre emergence in finger millet, Isoproturon (Arelon) @ 0.50-0.75 kg/ha as Pre emergence in Finger mille and kodo millet, Propazine (Propinex)@ 0.28-0.56 kg/ha as Pre emergence in Proso millet are recommended herbicides in minor millets. Atrazine was the most commonly used preemergence herbicide for weed control in millets.…”
Section: (D) Chemical Methodsmentioning
confidence: 99%
“…Chemical method is the most viable method of weed control in crops. However, rely on chemicals alone for weed management is not advisable due to its ill effects on environment and development of herbicide resistance in weeds (Sneha and Raj [24]). To effectively address this challenge, it is imperative to diminish reliance on singular or limited weed control methods.…”
Section: Introductionmentioning
confidence: 99%